Meningkatkan Kemampuan Memahami Unsur-Unsur Iklan dengan Menerapkan Metode Discovery Learning - Dewi, Ni Putu Ayu Kartika Sari; Subaker, I Wayan; Adni, Nissa Puspitaning (Attractive : Innovative Education Journal, 2022)
In an effort to improve students' abilities, various learning methods can be applied, one of which is the discovery learning method. The article aims to increase the understanding of advertising elements through applying discovery learning method. This discovery learning method students learn more actively and have more opportunities to be able to express themselves through the activities they do. Observation method was used to get data about students' attitudes. The test method is used to determine the students' ability to understand the elements of advertising by applying the discovery learning method to the students of class VIII D State Junior High School 3 Tabanan in the 2021/2022 academic year after applying the discovery learning method. The increase in the score is a sign that the ability to understand the advertising elements of class VIII D students of State Junior High School 3 Tabanan for the 2021/2022 academic year is getting better after applying the discovery learning method. Thus, it is recommended for Indonesian language teachers to apply the discovery learning method in learning and learning activities because it has been proven that the application of the discovery learning method can improve students' abilities. Keywords: Understanding Advertising Elements, Applying Discovery Learning, Students Ability